2008
DOI: 10.1530/eje-07-0836
|View full text |Cite
|
Sign up to set email alerts
|

Centrally located body fat is related to appetitive hormones in healthy postmenopausal women.

Abstract: Objective: Body composition and energy homeostasis are thought to affect the appetitive hormones: adiponectin, leptin, insulin, and ghrelin. This study examined whether centrally located fat and/or overall adiposity were related to these appetitive hormones in healthy postmenopausal women. Design: Overall and regional body composition was assessed by dual-energy X ray absorptiometry in relation to plasma adiponectin, serum leptin, serum insulin, and plasma ghrelin in 242 postmenopausal women. Results: Regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…One study revealed that waist-to-hip ratio was even more strongly associated with adiponectin than visceral fat tissue (6), which may be due to the additional effect of femoral-gluteal fat tissue (measured by hip circumference) on adiponectin levels. To our knowledge, only few studies have investigated regional fat distribution by DXA in relation to adiponectin levels in adults, one in men (32) and two in women (33,34). Consistent with our findings, it was found that lower body fat was positively associated with adiponectin levels (32,33).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One study revealed that waist-to-hip ratio was even more strongly associated with adiponectin than visceral fat tissue (6), which may be due to the additional effect of femoral-gluteal fat tissue (measured by hip circumference) on adiponectin levels. To our knowledge, only few studies have investigated regional fat distribution by DXA in relation to adiponectin levels in adults, one in men (32) and two in women (33,34). Consistent with our findings, it was found that lower body fat was positively associated with adiponectin levels (32,33).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our findings, it was found that lower body fat was positively associated with adiponectin levels (32,33). In the third study, the androidal-to-gynoidal fat mass ratio assessed via DXA accounted for the greatest part of the variability in adiponectin levels (34). An explanation for the different associations of trunk and leg fat with adiponectin levels may be that these fat depots may differ in adiponectin secretion rate.…”
Section: Discussionsupporting
confidence: 86%
“…Both studies assessed visceral fat using a 2D technique that does not allow precise quantification of fat mass. Other studies have assessed the impact of abdominal fat on ghrelin levels by measuring waist circumference (WC) (16), DXA (2) or by a combination of WC and DXA (9). Although these techniques are useful when studying large cohorts and expose trial subjects to minimal radiation, they do not accurately assess the amount of visceral fat.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in postmenopausal women reports an inverse relationship with abdominally located fat (9), whereas others report a positive correlation with visceral fat (10). Highlighting some of the difficulties when comparing body composition studies, the former study used dual X-ray absorptiometry (DXA) to measure abdominal fat, a technique unsuited to differentiate between abdominal s.c. and visceral fat.…”
Section: Introductionmentioning
confidence: 99%
“…In reference to most of the adipokines, Ritland et al [39] observed that centralized body fat was the main contributor to each circulating appetitive hormone in healthy postmenopausal women: androidal-to-gynoidal fat mass ratio (adiponectin), android fat mass (leptin), sagittal abdominal diameter (insulin), or waist circumference (ghrelin) ghrelin. …”
Section: Leptin/adiponectinmentioning
confidence: 99%